Market orientation and corporate performance of small and medium-sized enterprises in Saudi Arabia - Nabil Mohamed Abdo Alabsy (Innovative Marketing)
The goal of this paper is to examine the effect of business orientation on the success of small and medium-sized enterprises in Saudi Arabia. Corporate performance is a dependent variable, whereas business orientation, competitor orientation and inter-functional orientation are used as independent variables. This cross-section analysis was based on a quantitative survey design. The target population consisted of 72 SMEs (industrial, commercial and service) identified by the Saudi Chamber of Commerce in Riyadh. The companies were selected from Riyadh, Jeddah, Abha, Dammam and Bisha, which were founded before March 1, 2005 with less than 100 employees in Saudi Arabia. The findings showed that consumer orientation, competitor orientation and inter-functional cooperation had a substantial positive influence on the success of SMEs in Saudi Arabia during the study period. Market orientation dimensions, in particular, demonstrated a modest relationship to company efficiency. It was concluded that the greater the orientation of the business, the higher the output and the income of the enterprises. SME owners/managers are advised to understand the consumer orientation dimensions that have a positive effect on the success of their firms. Involved parties also need to establish more consistent business-oriented strategies that assess corporate success in order to boost the output of Saudi companies.